Should digital taxation be in sync with the OECD-G20 Two-Pillar Framework? An Analysis of the Equalization Levy in India and Its Aftermath. - Paul, Arun; Ramalingam, N (Gyan Management Journal, 2023)
The flourishing growth of the digital economy in India has made digital taxation an indispensable system in India’s revenue generation. The study provides a detailed assessment of the OECD (Organization for Economic Cooperation and Development)- G20(Group of 20) group’s initiatives on digital economy taxation. Furthermore, there is an in-depth analysis of the limitations of the Indian ‘Income Tax Act 1961’ and the subsequent adoption of the equalization levy. The effect of equalization levies on tax treaties, rules, and the General Agreement on Trade in Services (GATS) are examined in detail. The economic impact of the equalization levy is also evaluated by analyzing the digital trade restrictiveness index. Finally, an evaluation is carried out on the OECD- G20 Two-Pillar framework on the background of the problems of digital taxation. The study also examines the growth of the equalization levy in India and assesses the USTR (United States Trade Representative) report in light of the equalization levy.